Androgen/Androgen Receptor Signaling in Ovarian Cancer: Molecular Regulation and Therapeutic Potentials - Chung, Wei-Min (Int J Mol Sci, 2021)
Ovarian cancer (OVCA) arises from three cellular origins, namely surface epithelial cells, germ cells, and stromal cells. More than 85% of OVCAs are EOCs (epithelial ovarian carcinomas), which are the most lethal gynecological malignancies. Cancer stem/progenitor cells (CSPCs) are considered to be cancer promoters due to their capacity for unlimited self-renewal and drug resistance. Androgen receptor (AR) belongs to the nuclear receptor superfamily and can be activated through binding to its ligand androgens. Studies have reported an association between AR expression and EOC carcinogenesis, and AR is suggested to be involved in proliferation, migration/invasion, and stemness. In addition, alternative AR activating signals, including both ligand-dependent and ligand-independent, are involved in OVCA progression. Although some clinical trials have previously been conducted to evaluate the effects of anti-androgens in EOC, no significant results have been reported. In contrast, experimental studies evaluating the effects of anti-androgen or anti-AR reagents in AR-expressing EOC models have demonstrated positive results for suppressing disease progression. Since AR is involved in complex signaling pathways and may be expressed at various levels in OVCA, the aim of this article was to provide an overview of current studies and perspectives regarding the relevance of androgen/AR roles in OVCA.